PREVALENCE, ETIOLOGY, MODERN DIAGNOSTICS, AND TREATMENT METHODS OF PYOMETRA IN DOGS (European Journal of Interdisciplinary Research and Development, 2025)
Pyometra is a common reproductive organ disease in dogs, often beginning with mild clinical signs but posing a serious threat to the animal’s life if not treated in time. Although studies conducted in recent years have contributed to a better understanding of this condition, hypotheses regarding the etiology of pyometra — including the role of bacteria, pre-existing uterine lesions, and even dietary factors — indicate that this disease requires further in-depth investigation. Considering these aspects, this article provides information on the etiology, modern diagnostic methods, and treatment approaches of pyometra based on a review of the scientific literature.